BONE MINERAL DENSITY IN PATIENTS WITH CHRONIC LOW BACK PAIN: Bone Mineral Density - Aziz, Tariq; Jilani, Saira; Khan, Atif Ahmed; Ahmad, Mahmood; Iqbal, Sara; Shafaat, Hina Kanwal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine mean bone mineral density in patients with chronic low back pain presenting at Armed Forces Institute of Rehabilitation Medicine Rawalpindi based on dual energy x-ray absorptiometry studies. Study Design: Cross sectional study. Place and Duration of Study: Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi from Apr 2015 to Mar 2016. Patients and Methods: Two hundred and forty patients having low back pain of more than 6 months duration fulfilling the inclusion criteria were included both from indoor and outdoor departments through non-probability consecutive sampling. Bone mineral density was measured at lumbar spine by dual energy x-ray absorptiometry studies by the same technical staff using the same equipment. A written informed consent was taken from each patient. Data were collected and recorded on specialized proforma by the principal investigator. Results: Spine BMD on DXA scan ranged from 0.90 to 0.98 g/cm2 with a mean of 0.95 ± 0.02 as shown in. When stratified, the mean BMD decreased significantly with increasing age and severity of LBP; 20-30 years vs. 31-40 years (0.95 ± 0.01 vs. 0.92 ± 0.02; p=0.001). However, there was no significant difference in mean BMD across genders; male vs. female (0.94 ± 0.01 vs. 0.94 ± 0.02; p=0.680). Similarly there was no significant difference in mean BMD across various durations of low back pain; 7-10 vs. 11-14 months (0.94 ± 0.03 vs. 0.93 ± 0.01; p=0.617). Conclusion: The mean bone mineral density at spine was found to be lower in patients with chronic low back pain. It was significantly lower in older patients and those with severe low back pain. However, it didn’t change significantly with various durations of low back pain or gender.